Transformative Learning for the Development of Student Activists’ Spirit of Social Entrepreneurship - Sunanik, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
Every individual goes through the learning process. The output of the learning process are the changes in behavior both in the cognitive, affective and psychomotor domains. One of the outcomes of joining student organizations is the formation of soft skills in students. This study aims to describe the values possessed by student activists of the STKIP PGRI Tulungagung Student Activity Units (SAUs) and to propose a Social Entrepreneurship (SE) training which utilizes transformative learning method for those students. The research method used is descriptive-qualitative, and the object under study is the soft skill possessed by student activists of the Student Activity Units (SAUs) of STKIP PGRI Tulungagung. Data collection method is in-depth interviews, the research instrument is the researcher, and the data analysis technique uses the Grounded Theory method. The conclusions of this study are as follow: 1. Student activities in the student activity unit (SAUs) can shape students’ soft skills and provide an understanding of social activities that provide experience and form a sense of togetherness, a sense of solidarity, and the unity to advance together in helping people who face problems. 2. Transformative learning is expected to be an alternative learning model employed in social entrepreneurship training programs for SAUs student activists. The SE training help generates a community where social issues are transformed into social acts and develops students’ engagement with the field at large and fellow actors and provides an invigorating creative environment.